Cereal grain and ear detection with convolutional neural networks - Mäkinen, Joonas (My University, 2020)
High computing power and data availability have made it possible to combine traditional farming with modern machine learning methods. The profitability and environmental friendliness of agriculture can be improved through automatic data processing. For example, applications related to computer vision are enabling automation of various tasks more and more efficiently. Computer vision is a field of study which centers on how computers gain understanding from digital images. A subfield of computer vision, called object detection focuses on mathematical techniques to detect, localize, and classify semantic objects in digital images. This thesis studies object detection methods that are based on convolutional neural networks and how they can be applied in precision agriculture to detect cereal grains and ears. Cultivation of pure-oats poses particular challenges for farmers. The fields need to be inspected regularly to ensure that the crop is not contaminated by other cereals. If the quantity of foreign cereals containing gluten exceeds a certain threshold per kilogram of weight, that crop cannot be used to produce gluten-free products. Detecting foreign grains and ears at the early stages of the growing season ensures the quality of the gluten-free crop.

Suuri laskentateho ja tiedon saatavuus ovat mahdollistaneet modernien koneoppimismenetelmien käytön perinteisen maanviljelyn yhteydessä. Maatalouden kannattavuutta ja ympäristöystävällisyyttä voidaan parantaa automaattisen tietojenkäsittelyn avulla. Yhä useampia tehtäviä voidaan automatisoida tehokkaammin esimerkiksi tietokonenäön avulla. Tietokonenäkö on tutkimusala, joka tutkii sitä, miten tietokoneet ymmärtävät digitaalisten kuvien sisältämää informaatiota. Hahmontunnistus on yksi tietokonenäön osa-alueista, jossa keskitytään matemaattisiin tekniikoihin, joiden avulla kuvista havaitaan, paikallistetaan ja luokitellaan hahmoja. Puhdaskauran viljely asettaa viljelijöille erityisiä haasteita. Pellot on tarkistettava säännöllisesti, jolla varmistetaan se, että sato ei ole muiden viljojen saastuttama. Satoa ei voida käyttää gluteenittomien tuotteiden tuottamiseen, jos gluteenia sisältävien viljojen määrä ylittää sallitun rajan painokiloa kohden. Gluteenittoman sadon laatu voidaan varmistaa varhaisessa vaiheessa havaitsemalla vieraiden lajien jyvät ja tähkät.
Keywords: Object detection, neural networks